The characteristics of PhD programs at Saint-Petersburg State University (SPSU): The transformation of generic competences of PhD students in Political Science - Maria Edinova (Universidad de Deusto, 2020)
The aim of this article is to explore the characteristics of the new model of PhD programs (using the case of SPSU) and to test the following hypothesis: the new model of PhD programs in Saint-Petersburg State University (SPSU) is relevant and useful for innovative development and knowledge economy formation. The hypothesis was tested according to the following tasks: 1) Analysis of the cooperation of main actors or dialog between actors in the case of the Faculty of Political Science (SPSU); 2) Estimate of changes in completion rates in the case of the Faculty of Political Science at SPSU; and 3) Exploration of the motivations of PhD students in the case of the Faculty of Political Science at SPSU. The new model of PhD programs affects the structure of communication and coordination channels between all stakeholders. It also supports the necessity of such incorporation channels for the development of educational programs. Network analysis shows that SPSU is the main actor in the decision-making processes for the development of methodological and scientific programs. Other governmental bodies, NGOs, and institutes are also included in this process. Discourse analysis and a review of questionnaire data show the first perceptions of the new model of PhD program. The new model is changing the completion rates by introducing a new measurement: the Diploma "Researcher. Teacher-Researcher". An overview of general competences at SPSU proved that core competences of this program correlate with soft skills and encourage the development of systematic and critical thinking, project management and cooperation skills. In addition they provide the possibility to build inter-cultural channels of self-development and to work with information. Received: 11 March 2019 Accepted: 17 March 2020 Published online: 19 May 2020